The political role of Muslim women in Shari`ah: an analysis - Osmani, Noor Mohammad (Bangladesh Institute of Islamic Thought (BIIT), 2014)
The Muslim scholars are in general agreement that women are not entitled to hold the topmost public office of a nation. Is that due to certain provisions in the Qur'an and Prophetic traditions (ahadith) or is it due largely to socio-cultural and economic settings of a country? The Qur'an urges women not to make dazzling display publicly as practiced during Jahiliyyah (33: 33). It also asserts that men are the protectors and maintainers of women (4: 34). The Prophetic tradition commonly cited in this regard is the saying attributed to him which proclaims: "No nation will ever prosper if a woman is assigned to its highest public office." (Bukhari, no. 4073, 6570). On the other hand, the Qur'an acclaims the Queen of Sheba for her just rule. Hence, some prominent scholars such as Imam Abu Hanifah, Tabari and Ibn Hazm support that women could hold the topmost judicial position. Ibn Hazm also asserts that in principle, it is conceivable that women can carry out the mission of Prophethood, and if they could be Prophets, they would also be leaders, for the Prophets are leaders. The present research is carried out to deal with this issue. It would primarily depend on the Qur'anic ayat, Prophetic traditions, heritage of Islamic Caliphs and the verdicts of Muslim jurists. The research will critically evaluate the validity of the quoted hadith, and examine the circumstances surrounding the said hadith to know its real perspective. It will make a comparative analysis between the classical and the contemporary scholars to see how the changing realities affected their stand on this crucial issue and what should be the objective standpoint on the political role of Muslim women.